2010
DOI: 10.1186/1741-7007-8-65
|View full text |Cite
|
Sign up to set email alerts
|

Gli2a protein localization reveals a role for Iguana/DZIP1 in primary ciliogenesis and a dependence of Hedgehog signal transduction on primary cilia in the zebrafish

Abstract: BackgroundIn mammalian cells, the integrity of the primary cilium is critical for proper regulation of the Hedgehog (Hh) signal transduction pathway. Whether or not this dependence on the primary cilium is a universal feature of vertebrate Hedgehog signalling has remained contentious due, in part, to the apparent divergence of the intracellular transduction pathway between mammals and teleost fish.ResultsHere, using a functional Gli2-GFP fusion protein, we show that, as in mammals, the Gli2 transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 47 publications
4
59
2
Order By: Relevance
“…Cilia length is regulated by cAMP levels (31,32). However, the observation that stable expression of Smo and GRK2 can affect cilia length is consistent with a previous suggestion that the Hh pathway by itself may influence the length of primary cilia (33). Surprisingly, GRK2 does not have to traffic into the cilia or to the basal body in order to exert its effect.…”
Section: Discussionsupporting
confidence: 67%
“…Cilia length is regulated by cAMP levels (31,32). However, the observation that stable expression of Smo and GRK2 can affect cilia length is consistent with a previous suggestion that the Hh pathway by itself may influence the length of primary cilia (33). Surprisingly, GRK2 does not have to traffic into the cilia or to the basal body in order to exert its effect.…”
Section: Discussionsupporting
confidence: 67%
“…(6). Recent studies have shown that zebrafish with either mutations in the Igu gene (the zebrafish Dzip1 homolog) or Igu morpholino knockdown lacks primary cilia (41)(42)(43). However, the underlying mechanism of the cilia defect is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos that lack functions of Ift88 or Talpid3 have no primary cilia and are deficient for high-level Hh signaling but have expanded low-level signaling (Ben et al, 2011;Huang and Schier, 2009), suggesting that in zebrafish, cilia promote efficient Hh signaling. To test whether or not primary cilia, independent of apical Par protein functions, are necessary for neural progenitor maintenance, we examined dzip1 mutant embryos, which lack primary cilia and have a Hh signaling profile similar to that of Ift88 and Talpid3-deficient embryos (Wolff et al, 2004;Sekimizu et al, 2004;Kim et al, 2010;Huang and Schier, 2009;Tay et al, 2010). At 3 and 5 dpf, dzip1 mutant animals had similar numbers of Sox2 + and PH3…”
Section: Apical Par Proteins Mediate the Effects Of Mir-219 On Hh Sigmentioning
confidence: 99%